Comparison of molecular diagnostic approaches for the detection and differentiation of the intestinal protist Blastocystis sp. in humans - Šloufová, Martina; Lhotská, Zuzana; Jirků, Milan; Petrželková, Klára J; Stensvold, C Rune; Cinek, Ondřej; Pomajbíková, Kateřina Jirků (Parasite (Paris, France), 2022)
Blastocystis is the most commonly found intestinal protist in the world. Accurate detection and differentiation of Blastocystis including its subtypes (arguably species) are essential to understand its epidemiology and role in human health. We compared (i) the sensitivity of conventional PCR (cPCR) and qPCR in a set of 288 DNA samples obtained from stool samples of gut-healthy individuals, and (ii) subtype diversity as detected by next-generation sequencing (NGS) versus Sanger sequencing. Real-time PCR resulted in more positive samples than cPCR, revealing high fecal load of Blastocystis based on the quantification curve in most samples. In subtype detection, NGS was largely in agreement with Sanger sequencing but showed higher sensitivity for mixed subtype colonization within one host. This fact together with use of the combination of qPCR and NGS and obtaining information on the fecal protist load will be beneficial for epidemiological and surveillance studies.
Keywords: blastocystóza; Feces; Pathology, Molecular; Conventional-PCR; NGS; Blastocystis Infections; Blastocystis; Sensitivity; qPCR; lidé; kvantitativní polymerázová řetězová reakce; molekulární patologie; Quantification; feces; Humans; Real-Time Polymerase Chain Reaction